Genetic improvement and related activities. Improvement of individual characters. Resistance to fungal and bacterial diseases - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Main activities conducted during 1986 regarding the improvement of individual characters in bean comprised the evaluation of several advanced and segregating bean nurseries for their reactions under field conditions to rust, angular leaf spot, anthracnose, common bacterial blight, and halo blight as well as the development of methodologies to better determine disease resistance mechanisms. Results of these evaluations are included. (CIAT)